Manure applications alter the abundance, community structure and assembly process of diazotrophs in an acidic Ultisol - Lin, Yongxin; Ye, Guiping; Hu, Hang-Wei; Fan, Jianbo; He, Ji-Zheng (Frontiers in Microbiology, 2022)
The excessive usage of nitrogen (N) fertilizer can accelerate the tendency of global climate change. Biological N fixation by diazotrophs contributes substantially to N input and is a viable solution to sustainable agriculture via reducing inorganic N fertilization. However, how manure application influences the abundance, community structure and assembly process of diazotrophs in soil aggregates is not fully understood. Here, we investigated the effect of manure amendment on diazotrophic communities in soil aggregates of an arable soil. Manure application increased soil aggregation, crop yield and the abundance of nifH genes. The abundance of nifH genes increased with the increase of aggregate sizes, indicating that diazotrophs prefer to live in larger aggregates. The abundance of nifH genes in large macroaggregates, rather than in microaggregates and silt and clay, was positively associated with plant biomass and crop yield. Both manure application and aggregate size did not alter the Shannon diversity of diazotrophs but significantly changed the diazotrophic community structure. The variation of diazotrophic community structure explained by manure application was greater than that by aggregate size. Manure application promoted the relative abundance of Firmicutes but reduced that of α-Proteobacteria. Stochastic processes played a dominant role in the assembly of diazotrophs in the control treatment. Low-rate manure (9 Mg ha–1) application, rather than medium-rate (18 Mg ha–1) and high-rate (27 Mg ha–1) manure, significantly increased the relative importance of deterministic processes in diazotrophic community assembly. Taken together, our findings demonstrated that long-term manure application increased nifH gene abundance and altered the community structure and assembly process of diazotrophs in soil aggregates, which advanced our understanding of the ecophysiology and functionality of diazotrophs in acidic Ultisols.